1973
DOI: 10.1161/01.cir.48.6.1299
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in the Papago Indians

Abstract: A study of blood pressure in Papago Indians was undertaken utilizing a computerized health information system. Hypertension was present in close to 20% of the study population. The prevalence of hypertension in the -Papago tended to peak during young adulthood and showed very little increase in older age groups. The rates of cardiac, cardiovascular and renal complications were analyzed for the hypertensive and nonhypeertensive Papago. Hypertension was associated with increased morbidity from target organ damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Studies conducted between 1953 and 1993 show that lower blood pressures and reduced prevalence of hypertension are characteristic among American Indians and Alaska natives (19)(20)(21)(22)(23)(24)(25) and that American Indians have rates significantly lower than those of their counterparts among the general U.S. population (26). Although they are comparatively low, it is important to note that mean blood pressure and hypertension rates are higher in those with diabetes (8).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted between 1953 and 1993 show that lower blood pressures and reduced prevalence of hypertension are characteristic among American Indians and Alaska natives (19)(20)(21)(22)(23)(24)(25) and that American Indians have rates significantly lower than those of their counterparts among the general U.S. population (26). Although they are comparatively low, it is important to note that mean blood pressure and hypertension rates are higher in those with diabetes (8).…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports starting in the 1950s and extending to the present support the concept that hy pertension is as common in many Indian tribes as in the surrounding Anglo popula tion [51][52][53][54][55]. For example, Strotz and Shore [55] observed that approximately 20% of Papago Indians age 15 years and older had hypertension defined as a blood pressure in excess of 160/95 mm Hg. Moreover, these authors noted that hypertension was almost three times more common in diabetic than in nondiabetic patients.…”
Section: Hypertensionmentioning
confidence: 89%
“…Review of the literature disclosed two relevant research studies on hypertension in the Native American population. Hypertension was present in 20% of the study population of Papago Indians; the prevalence tended to peak during young adulthood (Strotz & Schorr, 1973). Navajo Indians had lower blood pressures and lower prevalence of hypertension than the white and black populations in the United States, according to DeStefano, Coulehan, and Wiant (1979).…”
mentioning
confidence: 86%